The Role of the Digital Economy in Shaping Sustainable Development in Ukraine's Regions - ZRYBNIEVA, IRYNA (Journal of Applied Economic Sciences, 2025)
This article systematically synthesizes empirical evidence on the influence of the numerical economy on the economic, social, and conservational dimensions of supportable progress in Ukraine’s regions. The paper aimed to integrate existing findings, identify key determinants of digital transformation effectiveness, and formulate practical policy recommendations at the regional level. The investigation was effectuated by using the PRISMA protocol systematic review, with searches performed in Scopus, Web of Science, SpringerLink, ScienceDirect, Google Scholar, and selected Ukrainian publications from 2019 to 2025. Clear inclusion and exclusion criteria, thematic mapping, and qualitative synthesis were applied, resulting in a final dataset of 25 studies. The findings indicate that the digital economy generally enhances productivity, entrepreneurial activity, energy efficiency, and the adoption of green innovations, while also expanding social inclusion through digital public services and education. At the same time, persistent disparities remain in access and competencies, with institutional gaps in decentralisation, uneven innovation capacities, and asymmetries in restoring critical infrastructure. The most significant determinants of impact include the quality of digital infrastructure and connectivity, population and SME digital literacy, agglomeration and sectoral renewal effects, efficiency of e-services, and the consistency of regulatory and budgetary support. The study proposes a policy package prioritizing broadband and smart networks in rural and war-affected communities,targeted skills programs, incentives for green technologies and R&D, strengthened digital public services, integration of social inclusion and mental health in digital strategies, and alignment of foreign investment with environmental standards.
Keywords: digital transformation; regional disparities; green innovation; social inclusion; post-war recovery